Untangling the Threads: Ethnographic reflexivity in a mining (mis)encounter (Pascua Lama 2000-2021, Chile) - Gajardo, Anahy (2025)
Mining contexts involving Indigenous peoples have become complex terrains for ethnographic research, marked by a high degree of politicisation, conflict, and a dense landscape of social actors. As spaces of both encounter and dissonance, or misencounter, between asymmetrical actors, these settings demand a critically situated reflection on the positionality of the researcher, the purposes of the research, and the forms of engagement adopted in the field. This article is situated within the socio-environmental conflict surrounding the Pascua Lama binational mining project (2000- 2021), alongside the simultaneous process of political and legal recognition of the Diaguita of Huasco Alto as an Indigenous people (Atacama Region, north of Chile). Drawing on long-term ethnographic research, this text reflects on the methodological, ethical, and epistemological challenges of fieldwork in Indigenous and extractive contexts. It explores the forms of engagement that emerge in anthropological practice as scholars navigate the tensions between critical distance, political commitment, and suspicions of academic extractivism.